IMPACT OF ORAL PROBIOTIC THERAPY ON MODULATION OF SUBGINGIVAL MICROBIOTA AND RESPONSE TO CONVENTIONAL PERIODONTAL TREATMENT - dos Santos, Pedro Guimarães Sampaio Trajano; Silva, Luciano Barreto; Travassos, Rosana Maria Coelho; do Nascimento, Alexandre Batista Lopes; da Paz, Eliana Santos Lyra; de Araújo, Vanessa Lessa Cavalcanti; de Menezes, Maria Regina Almeida; Alves, Josué; Cavalcanti, Maria Tereza Moura de Oliveira; Guaraná, Carlos Fernando Rodrigues; Silva, Kaick Mascarenhas de Santana Lima; Lopes, Daniela Siqueira (ARACÊ, 2025)
Objective: The objective of this narrative literature review article is to address the use of probiotics as an adjunct in the conventional treatment of periodontal diseases and how this remodels the subgingival microbiota. Methodology: The work of Rother (2007) was the study selected as a guide, an article that addresses systematic and narrative reviews, describing both, highlighting their characteristics and differences, contributing to the formation of the present study. In addition, to acquire the maximum amount of rich and scientifically proven information, searches were made in the following online databases: The Cochrane Library; ScienceDirect; Elsevier; COCHRANE; PubMed; Scielo and Google Academy. To acquire only articles and studies related to the topic addressed in the present study, the following keywords were used within the listed databases: Probiotics; Periodontitis; Periodontal Diseases; Microbiota. Results: Studies have analyzed the use of probiotics as an adjunct to periodontal treatment, where probiotic strains such as those of the Lactobacillus and Bifidobacterium genera have demonstrated the ability to reduce pocket depth in addition to increasing periodontal clinical parameters. The effects occur through mechanisms, through factors such as: competitive inhibition of periodontal pathogens, modulation of the host's immune response and the production of antimicrobial substances. Conclusion: Studies have shown promising results on the use of probiotics as adjuncts to conventional periodontal treatments; however, there is a clear need for more randomized clinical trials in order to establish a standardization on the use of these probiotics, in addition to studies that seek to analyze whether there are future consequences derived from the use of these probiotics.